2019
DOI: 10.1016/j.ctro.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarction after fractionated stereotactic radiation therapy of benign anterior skull base tumors

Abstract: Highlights Cerebral infarction is common after FSRT of benign anterior skull base tumors. Cerebral infarction is not more common after FSRT than in the general population. Special attention should be paid to cerebral vasculature, during dose planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Ullrich et al (29) observed that, Moyamoya was diagnosed in 12 of 345 patients (3.5%), at a median follow-up of 54 months after XRT for brain tumors. CI or ischemic stroke after XRT of a skull base tumor, is usually a delayed event (28,(32)(33)(34)(35)(36) and most of the patients in a study of Astradsson et al (37) had a stroke with onset several years after XRT. Tumors of the anterior skull base are located close to anatomical structures such as the Circle of Willis and the cavernous sinus, so that collateral XRT of these structures may occur and lead to vascular sequelae (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Ullrich et al (29) observed that, Moyamoya was diagnosed in 12 of 345 patients (3.5%), at a median follow-up of 54 months after XRT for brain tumors. CI or ischemic stroke after XRT of a skull base tumor, is usually a delayed event (28,(32)(33)(34)(35)(36) and most of the patients in a study of Astradsson et al (37) had a stroke with onset several years after XRT. Tumors of the anterior skull base are located close to anatomical structures such as the Circle of Willis and the cavernous sinus, so that collateral XRT of these structures may occur and lead to vascular sequelae (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion of the carotid artery or its branches leading to cerebral infarction or ischemic stroke is a potentially serious and life-threatening complication after stereotactic radiation therapy involving the extra-or intracavernous portion of the carotid artery or the Circle of Willis [67]. Although considered to be relatively rare, radiation-induced cerebral infarction has been reported after single fraction stereotactic radiosurgery or radiation therapy of meningiomas, pituitary adenomas, craniopharyngiomas, and vestibular schwannomas, with an occurrence of 1-7% [24,46,68,69,70]. However, the risk of cerebral infarction may not be increased when compared with the incidence in the general population.…”
Section: Cerebral Infarctionmentioning
confidence: 99%
“…However, the risk of cerebral infarction may not be increased when compared with the incidence in the general population. Predisposing risk factors identified for ischemic events are smoking, hypertension, and hyperlipidemia, as well as increased age [70]. Cerebral infarction is by definition a clinical diagnosis; therefore, subclinical infarctions only detectable by neuroimaging may occur [70].…”
Section: Cerebral Infarctionmentioning
confidence: 99%